Growth Respone of Bara Variety (Capsicum Frustencens) to Heavy Metal Stress of Cadmium Sulfate (CdSO4) - Oktaviani, Riska; Mukarlina; Linda, Riza (Jurnal Biologi Tropis, 2024)
Cadmium is a non-essential heavy metal that is toxic to plants. This study aims to determine the growth response of cayenne pepper var bara plants on planting media treated with different concentrations of cadmium sulfate heavy metal stress (CdSO4). This research was conducted at the Biology Laboratory of the Department of Biology, Faculty of Mathematics and Natural Sciences, Tanjungpura University Pontianak, Chlorophyll Test was conducted at the Integrated Biology Laboratory UPT, Tanjungpura University Pontianak, and soil analysis tests were conducted at the Chemistry and Soil Fertility Laboratory, Faculty of Agriculture, Tanjungpura University, Pontianak. This study used a completely randomized design (CRD) with 4 treatment levels of cadmium sulfate concentration, namely control (0 ppm), 80 ppm, 120 ppm, and 160 ppm. Data were analyzed using one-way Anova followed by Duncan test with 95% confidence level. The results showed that the administration of heavy metal cadmium sulfate (CdSO4) at the lowest concentration of 80 ppm had a significant effect on the growth of cayenne pepper var bara, namely leaf area, dry weight and chlorophyll content, while the 120 and 160 concentration treatments had a significant effect on the growth of cayenne pepper var bara plants, namely plant height, and wet weight.